PERBANDINGAN KINERJA PERBANKAN INDONESIA STUDI PADA BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2017 - Handriyani Dwilita (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2019)
The title of this study is a Comparative Analysis of Financial Performance at Islamic Bank and Conventional Commercial Bank Listed on the Indonesia Stock Exchange for the Periode of 2008-2017. This study aims to examine and find out more clearly how the comparison between Financial Performance at Islamic Bank and Conventional Commercial Bank. This study uses a comparative method involving nine (9) Islamic Bank and seven (7) Conventional Commercial Bank. The data used is secondary data.The data obtained were analyzed using a statistical formula, namely by using a comparative analysis of the management carried out with the spss version 32. The result of the correlation analysis are: mean values of CAR of Syariah Bank 31,7376 andBank Syariah 16,6391. This explains the CAR value of a Sharia Bank is higher than a Conventional Commercial Bank with a significant difference. Islamic Bank NPF Value 2.0793 and NPL of Conventional Commercial Banks 2.0559. This explains that the NPL value of Conventional Commercial Banks is better than Islamic Banks withinsignificant differences. The mean value of ROA of Islamic Banks 1.8156 and Conventional Commercial Banks 2.4514. This explains the value of ROA of Conventional Commercial Banks is higher than Islamic Banks with insignificant differences. The mean value of Islamic Bank BOPO 198,1737 and Conventional Commercial Banks 2910.15991. This explains that the BOPO value of Conventional Commercial Banks is better than Islamic Banks with significant differences. The mean value of Islamic Bank FDR 98.7462 and mean LDR Conventional Commercial Banks 83.6649. This explains that the FDR value of Sharia Banks is higherthan Conventional Commercial Banks with insignificant differences.